Roman Mosaics in the J. Paul Getty Museum - Belis, Alexis (Book collections on Project MUSE., 2016)
"A survey of all the mosaics in the J. Paul Getty Museum's collection, documenting their physical features as well as the contexts of their discovery and excavation across Rome's expanding empire--from its center in Italy to provinces in southern Gaul, North Africa, and ancient Syria"--Provided by publisher.